Heterospecific Nest Site Copying Behavior in a Wild Bird: Assessing the Influence of Genetics and Past Experience on a Joint Breeding Phenotype - Morinay, Jennifer; Forsman, Jukka T.; Kivelä, Sami M.; Gustafsson, Lars; Doligez, Blandine (Frontiers in Ecology and Evolution, 2018)
Breeding site selection is often a joint decision of pair members in species with biparental care and the experience of both pair members may influence the use of information for site selection. Nevertheless, quantitative genetics of joint information use for site selection remains unexplored so far. We used an experimental approach to quantify the relative importance of genetics (heritability) and past experience (age, familiarity with the environment, previous breeding success, previous information use) in heterospecific social information use for nest site selection in wild collared flycatchers (Ficedula albicollis). Flycatchers collect social information from resident tits for nest site selection. We created an apparent preference of tits for a novel nest site feature and recorded choices of flycatchers (copying or rejecting the tit preference). Copying behavior was stronger for naive individuals but also differed between years, which could be explained by contrasting seasonality in the demonstrator species. Past experience as reflected by age affected subsequent use of social information: pairs with a yearling male were more likely to copy the heterospecific preference than pairs with older immigrant males. There was no general pattern in successive individual choices over the years. Accordingly, individual repeatability in copying tit preference was very low. At the pair level, we estimated sex-specific direct and indirect genetic effects on the joint nest site decision and found no sex-specific heritability and no cross-sex genetic correlation. Our results confirm the importance of past experience for social information use and suggest that social information use is highly plastic and most likely not genetically inherited in collared flycatchers. Whether individuals use social information should be related to environmentally-induced changes in the quality of information and thus be context-dependent. Selection may therefore act on the ability to optimally use social information in varying environments and on the processes underlying such adjustment, such as learning, rather than the use of information itself.